Image based Digitisation of Entomology Collections: Leveraging volunteers to increase digitization capacity - Flemons, Paul (Pensoft Publishers, 2012)
Abstract. In 2010, the Australian Museum commenced a project to explore and develop ways for engaging volunteers to increase the rate of digitising natural history collections. The focus was on methods for image-based digitising of dry pinned entomology collections. With support from the Atlas of Living Australia, the Australian Museum developed a team of volunteers, training materials and processes and procedures. Project officers were employed to coordinate the volunteer workforce. Digitising workstations were established with the aim of minimising cost whilst maximising productivity and ease of use. Database management and curation of material before digitisation, were two areas that required considerably more effort than anticipated. Productivity of the workstations varied depending on the species group being digitised. Fragile groups took longer, and because digitising rates vary among the volunteers, the average hourly rate for digitising pinned entomological specimens (cicadas, leafhoppers, moths, beetles, flies) varied between 15 to 20 per workstation per hour, which compares with a direct data entry rate of 18 per hour from previous trials. Four specimen workstations operated four days a week, five hours a day, by a team of over 40 volunteers. Over 5 months, 16,000 specimens and their labels were imaged and entered as short records into the museum’s collection management database.